(untitled) (Fiep Bulletin - online, 2017)
Discussing the conceptions of body in the discourse of basic school teachers as well as their possible consequencesfor teaching is the aim of this paper, which stems from a wider research entitled “Body: teachers’ conceptions of the basiceducation”. The empirical field of research is formed by two schools of basic education located in Teresópolis, Rio de JaneiroState (Brazil); the participants are twenty-two teachers of the basic education, from different areas of knowledge, and the datawere collected through the WhatsApp application. We bring into this discussion the total of five conceptions, expressed in theextracts of two physical education teachers and three math teachers. The study is justified by the growing social and culturaldemands of thinking knowledge from an interdisciplinary perspective. Thus, our research question can be presented as it follows:what are the teachers’ conceptions of body in the basic education? Our discussions, focusing on the basic education sector, arebased upon the philosophical dimension as highlighted by Catarino (2013). The results underscore the complexity of teachingaction, since it is necessary to be aware of the various forms of demonstration of knowledge, considering necessary to useteaching dimensions as a way of intellectual autonomy, and students’ dimension to construct their own knowledge. Ourconclusion shows that the way we understand knowledge undergoes various influences throughout the construction of theidentity of the teacher, and it is not necessarily related to their formation in specific areas.